Artist Collaboration and Unity in Times of Crisis: The Spirals Project - Díaz Vicedo, Noèlia; Marini, Hari (Text Matters: A Journal of Literature, Theory and Culture, 2023)
The pandemic crisis of COVID-19 that we have recently endured, and that to some extent we are still experiencing, abruptly changed the way in which we conceive of the interaction between inner and outer space. Specifically, during the most difficult times caused by the two severe lockdowns, this limitation came complete with a total lack of spatial mobility. This article will explore the impact that this had upon the creative process of writing and making performance work for the female subject and how the return to the domestic space as the only possibility, affected their writing and creativity. Using the concept of the “nomadic subject” developed by Rosi Braidotti in 1996 and revised in 2011 in her book Nomadic Subjects: Embodiment and Sexual Difference in Contemporary Feminist Theory, this article aims to explore these questions from the intersection of body and language through the symbol of the spiral as a source of creation.